Predictors of harsh parenting practices and inter-partner conflict during the COVID-19 pandemic in Ontario, Canada: a cross-sectional analysis from the Ontario Parent Survey - Eric Duku; Divya Joshi; Andrea Gonzalez; Leslie Atkinson; Lil Tonmyr; Amir Aschner; Daniella Halili-Sychangco; Eve S Puffer; Amber Rieder (BMJ Open)
Objectives Guided by the bioecological model, the purpose of this study was to examine the associations of (1) individual level factors (sociodemographic, health behaviour and mental health), (2) family (micro) level COVID-19 experiences (difficulty with household management, managing child mood and behaviour, and pandemic-related positive experiences) and (3) community (macro) level factors (residential instability, ethnic concentration, material deprivation and dependency, an indicator of age and labour force) with harsh parenting practices and inter-partner conflict during the early lockdown of the COVID-19 pandemic in Ontario, Canada.Design A cross-sectional analysis of data from the Ontario Parent Survey.Setting A convenience sample of 7451 caregivers living in Ontario, Canada, at the time of baseline data collection (May–June 2020).Participants Caregivers aged 18 years and older with children 17 years or younger.Outcome measures Parenting practices over the past 2 months was assessed using a published modification of the Parenting Scale. The frequency of inter-partner conflict over the past month was assessed using the Marital Conflict scale.Results Individual (sociodemographic factors, alcohol use, and higher depressive and anxiety symptoms) and family (difficulties with managing the household and child mood and behaviour) level factors were positively associated with inter-partner conflict and harsh parenting practices. Having fewer positive experiences (eg, performing activities with children), and economic adversity at the family level were positively associated with inter-partner conflict but inversely associated with harsh parenting. At the community level, residential instability was negatively associated with harsh parenting practices.Conclusions Individual and family level factors were associated with harsh parenting and inter-partner conflict. The associations of fewer positive experiences and economic hardship with harsh parenting practices may be more complex than initially thought. Efforts that raise awareness and address caregiver mental health concerns are needed as part of the pandemic response to promote positive inter-partner and parent-child interactions.